Influência da adição de pó de retífica em uma matriz de cimento de fosfato de magnésio - Ribeiro, Daniel Véras (2006)
In the present work, the magnesium phosphate cement use feasibility in the organic and inorganic hazardous industrial wastes encapsulation and the grinding dust of clutch discs influence (hazardous waste - classroom I) in the final properties of composites and mortars formed by this kind of cement was evaluated. The magnesium phosphate cements are material formed from the reaction between the magnesium oxide and soluble phosphates in water, such as the ammonium dihydrogen phosphate, which becomes solid at the ambient temperature from the formation of hydrated phases in the material. They are extreme-fast setting time cements, which acquire high mechanical resistance at early ages, comparing to the ordinary Portland cement. Initially, it was obtained the reference composition proportion constituents (without the waste and sand), adding, later, waste in 10% to 40% contents in relation to the cement mass. These compositions were analyzed comparatively with regard to the reference sample (0%) in regards to the physical and mechanical characteristics, setting time, analysis of the phases formed by DRX and the microstructure (MEV), choising of the 3 more promising compositions (with 10%, 20% and 30% of waste), that were evaluated by leaching/solubilization tests. After to be approved, mortar specimens with the wastes contents chosen in the previous stages were been molded and analyzed by mechanical tests (axial compression and traction by diametrical compression), water absorption by capillarity (NBR 9779) and comment of the microstructure (MEV). Finally, the compositions and mortars were submitted to an artificially-accelerated aging process corresponding to 1 year to the verification of this waste containing matrix durability with the presence of waste. The analyses of the results showed that the magnesium phosphate cement has the capacity to encapsulate the grinding dust, resulting in composites classroom II-A.